LEARNING THE CREATION OF LEV NIKOLAEV TOLSTOY THROUGH A LITERARY NIGHT IN EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Literary night is also an important tool in determining students' inclinations and personal abilities. "Literary night," says V.V. Golubkov, "is a demonstration of the power of all circles: literary-creative, dramatic, expressive reading, and creative storytelling circles." Literary night at school should be aimed at a specific goal.